Spawning features of Kura chub Alburnoides eichwaldii (De Filippi, 1863) (Cyprinidae, Actinopterygii) in the basin of Debed and Aghstev rivers (Armenia) - A. S. Arakelyan (ՀՀ ԳԱԱ հրատ.)
Spawning features of Kura chub Alburnoides eichwaldii (De Filippi, 1863) distributed in the basin of Debed and Agstev Rivers have been studied. It has been revealed that the Kura chub in the basin of Debed and Agstev Rivers becomes mature at the beginning of the second year when it has no less than 60 mm body length. Ուսումնասիրվել են Դեբեդ և Աղստև գետերի ավազանում տարածված արևելյան տառեխիկի Alburnoides eichwaldii (De Filippi, 1863) բազմացման առանձնահատկությունները: Պարզվել է, որ Դեբեդ և Աղստև գետերի ավազաններում արևելյան տառեխիկի սեռահասունությունը վրա է հասնում մարմնի 60 մմ-ից ոչ պակաս երկարության և կյանքի երկրորդ տարվա սկզբում: Изучены особенности размножения восточной быстрянки Alburnoides eichwaldii (De Filippi, 1863) в бассейне рек Дебед и Агстев. Выяснено, что в изученных водоемах половозрелость быстрянки наступает при длине тела более 60 мм и в начале второго года жизни.
Keywords: Biology; Hydrobiology